A novel lever-type vibration isolator with eddy current damping. (3rd March 2021) - Yan, Bo; Wang, Zhihao; Ma, Hongye; Bao, Huihuang; Wang, Ke; Wu, Chuanyu
Highlights: A lever-type vibration isolator (LVI) is proposed, modeled, and analyzed. Transmissibility and natural frequency decrease with the increase in lever ratio. Eddy current damping (ECD) can improve vibration isolation performance of the LVI. Tip mass of the lever is beneficial for vibration isolation of the LVI-ECD. Material properties and cross-section have little effect on isolation performance. Abstract: This study proposes a lever-type vibration isolator with eddy current damping (LVI-ECD), which can broaden the isolation band by adjusting the lever ratio and improve the vibration suppression performance with eddy current damping (ECD). The LVI-ECD composes of a lever with a permanent magnet (PM) at the tip of the lever, a load plate, a base plate and springs, etc. The relative motion between the PM and the conductive base and load plates induces ECD, which can be amplified by the lever structure and thus to generate nonlinear damping effect. The theoretical models of the lever-type vibration isolator (LVI) and LVI-ECD are established and the amplitude frequency relationship considering nonlinear damping is deduced. The effects of the lever ratio, tip mass, material property and cross-section of the lever, geometric parameters of the PM and excitation amplitude on the vibration isolation performance of the LVI-ECD are analyzed. The analytical predictions are consistent with the experimental results, which demonstrates that the peak transmissibility and natural frequency decrease with the increase of the lever ratio. ECD can further improve the vibration suppression performance in the resonance region. The transmissibility tends to be flat with the increase of the lever ratio in the isolation region. The vibration isolation performance can be also improved by increasing the tip mass of the lever. The material property and cross-section of the lever have little effect on vibration isolation. This study provides a guideline to design, model and optimize a passive damped lever-type vibration isolator. Graphical abstract: Image, graphical abstract